2017
DOI: 10.1111/asj.12877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginkgo extract supplementation on in vitro rumen fermentation and bacterial profiles under different dietary conditions

Abstract: Ginkgo extract was applied to a batch culture study and evaluated for its potential as a feed additive for ruminant animals under different forage-to-concentrate (F:C) ratios (1:9, 3:7, 5:5, 7:3 and 9:1). Rumen fluid was mixed with respective diet and incubated at 39°C for 24 h with and without ginkgo extract (1.6% fruit equivalent in culture). Methane production was significantly decreased by ginkgo extract, with the greatest reductions found in the 5:5 (41.9%) followed by the 7:3 ratios (36.7%). Total short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Ginkgo ( Ginkgo biloba ) fruit extract was found to suppress methane production in the rumen by altering the rumen microbiota (Oh, Shintani, et al, 2017). This effect was consistent, irrespective of dietary conditions (Oh, Koike, & Kobayashi, 2017). As the preparation of ginkgo fruit extract is laborious and costly, a better option could be direct application of the fruit (which is considered a useless byproduct in the ginkgo nut industry) to cattle excreta.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Ginkgo ( Ginkgo biloba ) fruit extract was found to suppress methane production in the rumen by altering the rumen microbiota (Oh, Shintani, et al, 2017). This effect was consistent, irrespective of dietary conditions (Oh, Koike, & Kobayashi, 2017). As the preparation of ginkgo fruit extract is laborious and costly, a better option could be direct application of the fruit (which is considered a useless byproduct in the ginkgo nut industry) to cattle excreta.…”
Section: Introductionsupporting
confidence: 54%
“…Although changes in SCFA profiles with ginkgo fruit addition were not consistent, propionate in feces increased in proportion on Day 60 and after, whereas acetate was dominant in slurry (Table 2). Thus, ginkgo fruit addition can modulate excreta fermentation toward methane mitigation with changes in the SCFA profile, possibly by influencing the microbiota (discussed below), as described for rumen fermentation (Oh, Koike, & Kobayashi, 2017; Oh, Shintani, et al, 2017). Ginkgo fruit is a source of anti‐bacterial alkyl‐phenols, including anacardic acid, which selectively inhibits gram‐positive bacteria (Kubo et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The low abundance of Anaerovibrio, but the high abundance of Provetella_9, might contribute to the mass production of lactate and acetate during β -glucan and arabinoxylan fermentation. The enrichment of Anaerovibrio followed by the decreased proportion of lactate and acetate was also found in in vitro fermentation trials [ 40 , 41 ]. Another ability of Anaerovibrio was to ferment glycerol into propionate and succinate, among which was propionate produced by the dicarboxylic acid pathway [ 42 ].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, it remains unknown if Megasphaera or Selenomonas has any association or correlation with CH 4 emissions in the absence of anti-methane inhibitors. However, one in vitro study has shown that calcium salts of long-chain fatty acids 42 , tucuma oil 43 , and ginkgo extract 44 decreased CH 4 emissions while increasing propionate and the abundance of Megasphaera and Selenomonas . Encapsulated nitrate has also been found to reduce CH 4 emissions while increasing Selenomonas in steers 45 .…”
Section: Discussionmentioning
confidence: 99%